Porosity Prediction of Porous Materials Deposited by Semi-Molten Spraying Particles - Jian-Tao Yao; Hui Dong; Li-Shuang Wang (Metals, 2021)
To determine the relationship between the deposition characteristics of semi-molten particles and the porosity of porous materials prepared by flame spraying, metal powders of Mo and 316L were used and the melting degree of deposition particles was controlled. Based on the experimental observations, a three-dimensional, random-stacking model was established by introducing the slipping characteristics of semi-molten particles, which could help predict the porosity of the generated porous metal materials. The results show that the maximum porosity of porous materials deposited by semi-molten particles was about 82%. A one-to-one relationship was observed between the melting degree of particles and the porosity of deposited samples. The three-dimensional random model could successfully predict the porosity of porous materials by combining the melting degree and slipping characteristics of spray particles, and the predicted values were consistent with the experimental results. The results of this study are useful to control the pore structure of porous materials deposited by semi-molten spraying particles.